Intelectuais afro-periféricos e os coletivos de quebrada: a Lei 10.639/03 na pegada valandi à moda bandoleira - Santos, Thiago Lima Dos [UNIFESP] (2020)
This research deals with the intellectual production of knowledge and the training of teachers offered by two black collectives in the city of São Paulo, “BAOBÁ: : Fortificando as raízes” and “MALUNGO: Não deixe sua cor passar em branco”, about Law 10.639 / 2003. Having as objectives the analysis of that law, the description of the collectives and the analysis of their training actions as resistance to institutional racism present in the Brazilian educational system. The theoretical framework is based on black intellectuals that foment a deeper understanding about education and race relations. Following the path of these formations as an act of research- action. The sources are the course records, autobiographical nuances, memories and dialogues, which help us to highlight the emergence of Intelectuais Afro-Periféricos (Afro- Intellectuals from inner city).